COVID’s Razor: RAS Imbalance, the Common Denominator Across Disparate, Unexpected Aspects of COVID-19 - Czick M (Dove Medical Press, 2020)
Maureen Czick,1 Christine Shapter,2 Robert Shapter3 1University of Connecticut, Department of Anesthesia, Farmington, CT, USA; 2 University of Saint Joseph, West Hartford, CT, USA; 3Independent Consultant ( Medical Research, Medical Communications, and Medical Education), Hartford, CT, USACorrespondence: Maureen Czick Email meczick@yahoo.comAbstract: A modern iteration of Occam’s Razor posits that “the simplest explanation is usually correct.” Coronavirus Disease 2019 involves widespread organ damage and uneven mortality demographics, deemed unexpected from what was originally thought to be “a straightforward respiratory virus.” The simplest explanation is that both the expected and unexpected aspects of COVID-19 share a common mechanism. Silent hypoxia, atypical acute respiratory distress syndrome (ARDS), stroke, olfactory loss, myocarditis, and increased mortality rates in the elderly, in men, in African-Americans, and in patients with obesity, diabetes, and cancer—all bear the fingerprints of the renin-angiotensin system (RAS) imbalance, suggesting that RAS is the common culprit. This article examines what RAS is and how it works, then from that baseline, the article presents the evidence suggesting RAS involvement in the disparate manifestations of COVID-19. Understanding the deeper workings of RAS helps one make sense of severe COVID-19. In addition, recognizing the role of RAS imbalance suggests potential routes to mitigate COVID-19 severity.Keywords: ACE, ACE2, silent hypoxia, atypical ARDS, stroke, myocarditis